Impact of Nutritional Status on Postoperative Outcomes in Patients with Oral and Maxillofacial Malignancies - Mohammad Sayeem Rahman Bhuiyan, Md Saiful Azam, Md. Mostafizur Rahaman, Fazla Rubby Tymur, Md. Ruhul Kuddus, Abu Hena Helal Uddin Ahmed (South Eastern European Journal of Public Health, 2025)
Background: Nutritional status plays a critical role in postoperative outcomes for patients undergoing surgery for oral and maxillofacial malignancies. Malnutrition is common in these patients due to tumor-related dysphagia, metabolic alterations, and treatment-induced catabolic stress, increasing the risk of postoperative complications. This study aims to assess the impact of nutritional status on postoperative outcomes and highlight the need for perioperative nutritional management. Methods: This retrospective study analyzed 60 patients with oral squamous cell carcinoma (OSCC) who underwent surgery at the Oral & Maxillofacial Surgery Department of Bangabandhu Sheikh Mujib Medical University from January 1st to December 31st, 2020. Patients were categorized as well-nourished, moderately nourished, or malnourished based on preoperative clinical and biochemical parameters. Postoperative complications were classified into local (minor and major) and systemic. Statistical analysis included chi-square and Student’s t-tests, with p < 0.05 considered significant. Results: Postoperative complications occurred in 17 patients (28%), with a higher prevalence among malnourished individuals (53%). Malnourished patients experienced greater weight loss (-3.5 kg vs. -2.1 kg, p < 0.001) and more severe nitrogen depletion (-4.3 g/day vs. -2.6 g/day, p < 0.01). Although complications were more common in patients undergoing major surgeries, the difference was not statistically significant. Conclusion: Poor preoperative nutritional status significantly increased postoperative complications and worsened recovery outcomes. These findings underscore the importance of early nutritional assessment and perioperative nutritional support in reducing postoperative morbidity and optimizing surgical recovery in patients with oral and maxillofacial malignancies.